Assessment of the Brettanomyces bruxellensis metabolome during sulphur dioxide exposure. Issue 7 (30th July 2013) - Vigentini, Ileana; Lucy Joseph, C.M.; Picozzi, Claudia; Foschino, Roberto; Bisson, Linda F.
Abstract: Brettanomyces bruxellensis displays a high degree of genotypic and phenotypic polymorphism and is the main yeast species involved in wine spoilage. The innate resistance of 108 B. bruxellensis strains to the antimicrobial agent SO2 used in winemaking was investigated. Nineteen strains (17.6%) were sensitive to SO2, failing to grow at the lowest concentration tested (0.1 mg L −1 molecular SO2 ). Twenty‐nine strains (26.8%) grew at 0.1 mg L −1, 42 strains (38.9%) grew at 0.2 mg L −1, and 16 strains (14.8%) were able to grow as high as 0.4 mg L −1 mol. SO2 . Two strains able to grow in the presence of 0.6 mg L −1 mol. SO2 were further studied by GCMS‐TOF analysis to define the metabolic response to SO2 treatment. Two hundred and fifty‐three intracellular metabolites were detected. The main effect observed was a decrease in cytoplasmic levels of polyols and an increase in levels of some amino acids, alanine, glutamic acid, glycine, proline, 5‐oxoproline, serine and valine, which were significantly accumulated in the presence of SO2 . No alteration in the pentose phosphate pathway was observed, suggesting NADPH usage could be diverted to other pathways. Finally, a change in metabolites involved in the glycerophospholipid pathway (glycerol‐3‐phosphate and myo‐inositol) was also found.